Program Diet Berdasarkan Jenis Olahraga Berbasis Android - Ketut Wijaya Kusuma; Fatoni Fatoni; Hadi Syaputra (APTIKOM SUMSEL, 2020)
Sports is one of the physical activities that are good for health and fitness. By exercising, we can minimize the risk of developing disease. By exercising too, we can lose weight, keep our body weight stable and ideal, and many other benefits of exercise. Today, sports are carried out not only to lose weight or maintain health, but also as a means of recreation to channel hobbies as well as a profession. The problem now is that diet programs are still done manually and are not chosen properly, making it difficult for sportsmen to be able to undergo a diet program effectively because it is not in accordance with the type of exercise they are struggling with. Then an application is needed that can guide them to accompany an Android-based diet program